Advertising Effectiveness in Purchasing Decision on Instagram - Luh Putu Ayu Wulandari; Gede Sri Darma (Institut Pariwisata dan Bisnis Internasional, 2020)
The aim of this research is to observe the impact of advertising creativity, advertising appeal and endorser credibility to the advertising effectiveness and purchase decision on Instagram. This research was conducted in Ilsproject Store. It is an online and offline store in Denpasar which sells fashion product. The design of this research is a quantitative research which shows a causality relationship between variables. The technique of collecting data was done using questionnaire to 168 consumers. The technique of analyzing data was done using structural equation modeling (SEM) with the AMOS program version 22. The result of this research shows that the advertising creativity has a positive and significant impact of 0,783 to the advertising effectiveness and 0,203 to the purchase decision. The advertising appeal has a positive and significant impact of 0,783 to the advertising effectiveness and 0,648 to the purchase decision. The endorser credibility has a positive and significant impact of 0,803 to the advertising effectiveness and 0,656 to the purchase decision. The advertising effectiveness has a positive and significant impact to the purchase decision with the number 0,831.